Joint Symptoms, Aromatase Inhibitor-Related Adverse Reactions, Are Indirectly Associated with Decreased Serum Estradiol. (26th May 2011) - Honda, Junko; Kanematsu, Miyuki; Nakagawa, Misako; Takahashi, Masako; Nagao, Taeko; Tangoku, Akira; Sasa, Mitsunori
Abstract : Background . Joint symptoms (JSs) are problematic adverse drug reactions (ADRs) of aromatase inhibitors (AIs). Involvement of decreased serum estradiol (SE) has been suggested. Patients and Methods . 104 postmenopausal breast cancer patients administered an AI were prospectively investigated regarding various clinical parameters, JS and hot flashes as ADRs, and the SE level. Results . JS manifested in 31.7% of patients and hot flashes in 18.3%. Chi-square testing showed a significantly higher incidence of JS in several patient strata: <55 years old, decreased SE, and elevated total cholesterol (TC). In univariate analysis, JS correlated significantly with a pre-AI % YAM of ≥80%, decreased SE, and elevated TC. Eight (7.7%) patients maintained SE at ≥5 pg/mL for >6 consecutive months, with no JS. In chi-square testing, hot flashes showed a significantly higher incidence in patients <55 years old. Conclusion . AI-ADRs occurred more readily in younger patients. Decreased SE may be indirectly involved in JS.